1997
DOI: 10.1039/a702093g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterisation and reactivity of novel bis(tosyl)imidoruthenium(vi) porphyrin complexes; X-ray crystal structure of a tosylamidoruthenium(iv) porphyrin

Abstract: Bis(tosyl)imidoruthenium(VI) porphyrin complexes are prepared and characterised by spectroscopic means; [Ru VI -(tpp)(NTs) 2 ] can undergo imido group transfer reactions with alkenes to afford aziridines, as well as C-H bond oxidation of benzyl alcohol to give benzaldehyde; a tosylamido ruthenium(IV) complex is also isolated and characterised by X-ray diffraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 11 publications
3
13
0
Order By: Relevance
“…Subsequently, the synthetic utility of Ru­(II)–porphyrin catalysts in the amino group transfer was independently demonstrated by the groups of Cenini and Che . Importantly, the characterization of bis­(tosylimido)­Ru­(VI) porphyrin, which is an active intermediate for the C–H insertion, established a clear mechanistic foundation in this type of reaction. More recently, Gallo and co-workers synthesized an analogous Ru­(VI) complex 60 that displayed its capability to catalyze C–H amination in reaction with aryl azides (Scheme a and b). , Taking advantage of the thermal stability of complex 60 (stable for a long period of time at room temperature), mechanistic studies such as spectroscopic characterization were carried out. DFT studies led the authors to propose that two distinct catalytic cycles may be operative: one involving a monoimido Ru­(IV) species, and a second having a bisimido Ru­(IV) intermediate …”
Section: C–h Insertion Catalysissupporting
confidence: 61%
“…Subsequently, the synthetic utility of Ru­(II)–porphyrin catalysts in the amino group transfer was independently demonstrated by the groups of Cenini and Che . Importantly, the characterization of bis­(tosylimido)­Ru­(VI) porphyrin, which is an active intermediate for the C–H insertion, established a clear mechanistic foundation in this type of reaction. More recently, Gallo and co-workers synthesized an analogous Ru­(VI) complex 60 that displayed its capability to catalyze C–H amination in reaction with aryl azides (Scheme a and b). , Taking advantage of the thermal stability of complex 60 (stable for a long period of time at room temperature), mechanistic studies such as spectroscopic characterization were carried out. DFT studies led the authors to propose that two distinct catalytic cycles may be operative: one involving a monoimido Ru­(IV) species, and a second having a bisimido Ru­(IV) intermediate …”
Section: C–h Insertion Catalysissupporting
confidence: 61%
“…[23] Che reported mechanistic studies of stoichiometrici mido/nitreneg roup-transfer reactions by using bis(tosyl)imidoruthenium-porphyrinc omplexes such as Ru(TPP)(NTs) 2 . [24] Moreover, the amination of aC (sp 3 )ÀHb ond with iminoiodinanes hasa lso been investigated. Following seminalw ork by Breslow and Gellman, [19a, b] the next major advancesw ere achieved by Müller and co-workers.…”
Section: Iminoiodinanesmentioning
confidence: 99%
“…76 Highly enantioselective catalytic aziridinations of styrenes were realized by using (salen)manganese(III) complexes, 77 manganese and iron tetramethylchiroporphyrins, 78 and chiral rhodium(II) complexes. [79][80][81] An enhanced reactivity of PhINTs in the olefin aziridination reaction under achiral conditions was observed in the presence of the copper(II) complexes of pyridyl-appended diazacycloalkanes, 82,83 poly(pyrazolyl)borate-copper complexes, 84 the copper(II) complexes of 1,4,7-triisopropyl-1,4,7-triazacyclononane, 85 a Cu(I) complex of ferrocenyldiimine, 86 bis(tosyl)imidoruthenium(VI) porphyrin complexes, 87 and methyltrioxorhenium. 88 Mechanistic studies of copper-catalyzed aziridinations have demonstrated that copper nitrene species are the key intermediates in these reactions.…”
Section: Methodsmentioning
confidence: 99%
“…X-Ray crystal structures were determined for several bis(tosylimido)ruthenium(VI) and bis(tosylimido)osmium(VI) porphyrin complexes. 87,143,144 The reactivity of a cobalt(II) iminoiodane complex in hydrogen atom abstraction reactions has been investigated by Kundu and coauthors. 146 The in situ generated aziridine products can be easily transformed to heterocyclic compounds.…”
Section: Scheme 17mentioning
confidence: 99%